Intensitas Serangan Serangga Hama pada Terung (Solanum melongena L.) di Kabupaten Ogan Ilir, Sumatera Selatan - Fauziah Nabila; Mega Zakria Ferisya; Mita Ameilia; Novitasari J; Tia Ellisa Riyanti; Tiara Aprilya; Abu Umayah; Bambang Gunawan; Arsi Arsi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Nabila F, Ferisya MZ, Ameilia M, J Novitasari, Riyanti TE, Aprilya T, Umayah A, Gunawan B, Arsi A. 2022. Intensity of eggplant (Solanum melongena L.) insect pests attack in Ogan Ilir Regency, South Sumatera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 504-512. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The increase in the demand for eggplant production is not accompanied by an increase in the amount of production, which is caused by the low productivity of eggplant due to insect pests attack. This study aimed to determine the intensity of insect pests on eggplant in Ogan Ilir Regency, South Sumatra. The method used is a survey or observation in the field to observe the species of insect pests, symptoms, and the intensity of insect pests by taking 20 random plant samples (random sampling). This research was conducted on three fields with different locations. Insect pests found included mealybug (Planococcus citri), whitefly (Bemisia tabaci), leafhopper (Empoasca fabae), ladybug (Epilachna sparsa), weevil (Hypomeces squamosus), and tobacco cutworm (Spodoptera litura). Symptoms of the dominant pest attack in the form of hollow leaves caused by Spodoptera litura larvae. The level of damage from S. litura occured in the vegetative phase where the larvae eat young leaves. The data obtained were analyzed by One-Way ANOVA followed by the Honest Significant Difference (HSD) test at the 5% level. The results showed that the highest attack intensity of Spodoptera litura was in Timbangan Village (26.8 ± 1.92)% so that the attack rate could be categorized as high. The intensity of attacks in Permata Baru Village is (15.6 ± 2.70)% and the attack rate is categorized as medium. The smallest attack intensity was in Tanjung Pering Village (8.4 ± 12.07)% so that the attack rate was categorized as low.